Human Y chromosome and male enfertility: forward and back from azoospermia factor chromatin structure to azoospermia factor gene function - Vogt, Peter H.; Bender, Ulrike; Zimmer, Jutta; Strowitzki, Thomas (Genetics of human infertility, 2017)
In the euchromatic part of the long arm of the human Y chromosome (Yq11) at least 13 Y genes encoding proteins and expressed in male germ cells were found in 3 distinct genomic Y regions frequently deleted in infertile men with idiopathic azoospermia, i.e., for unknown reasons no mature sperm were found in their semen fluid. Accordingly, they were designated as azoospermia factor (AZF) regions: AZFa, AZFb, and AZFc. Additionally, 10 Y genes called “testis-specific transcript Y” (TTTY) genes were mapped in the same AZF intervals. They belong to the long non-coding RNA gene pool in human germ cells because they seem to lack any protein-coding potential. Distinct chromatin regions in Yq11 overlapping with AZFb and AZFc are supposed to be involved in the premeiotic X and Y chromosome pairing and inactivation process controlling male germ cell meiosis. It can thus be assumed that the germ line function of the AZF loci in Yq11 may be not only based on the expression of some germ cell proteins, but also on the expression of some germ cell-specific TTTY transcripts and a locally dynamic and specific chromatin folding structure probably controlled by some germ cell-specific nuclear proteins.
Gesehen am 29.07.2019